Inconsistent MHC class II association in Beagles experimentally infected with Leishmania infantum. (May 2018) - Soutter, F.; Martorell, S.; Solano-Gallego, L.; Catchpole, B.
Highlights: Individual variation to experimental infection with Leishmania infantum was observed in Beagles. DLA class II haplotypes were examined in Beagles experimentally infected with L. infantum . One DLA class II haplotype was associated with increased odds of sustained high positive Leishmania antibodies in one group. DLA class II genes were not associated with clinical leishmaniosis score in this study. Abstract: The clinical outcome of Leishmania infantum infection in dogs varies from subclinical infection to severe disease. Researchers attribute this variability in clinical manifestations to the ability of the immune response to limit pathogen multiplication and dissemination, which is, in part, likely determined by the immune response genes. The aim of this study was to test the hypothesis that MHC class II genes are associated with disease outcome of experimental L. infantum infection in Beagles. Dog leukocyte antigen (DLA) class II haplotypes were characterised by sequence-based typing of Beagle dogs experimentally infected with L. infantum during vaccine challenge studies. Variability of response to infection was determined by clinical score, serology and quantification of L. infantum DNA in the bone marrow over the study period. Dogs showed limited DLA diversity and the DLA profiles of dogs recruited for the different vaccine challenge studies differed. There were variable responses to infection, despite the apparent restriction in genetic diversity. One haplotype DLA-DRB1*001:02–DQA1*001:01–DQB1*002:01 was associated with increased anti- Leishmania antibodies in one infection model, but no DLA associations were found in other groups or with parasite load or clinical score. Examination of this particular DLA haplotype in a larger number of dogs is required to confirm whether an association exists with the immune or clinical responses to L. infantum infection.